Uji Mutu Benih Kedelai (Glycine max L. Merril) Varietas Grobogan yang Diproduksi dengan Aplikasi 10 Isolat PGPR - SUGIANTARI, NI PUTU NONIK; RAKA, I GUSTI NGURAH; UTAMI, UTAMI (Agrotrop : Journal on Agriculture Science; Vol 7 No 2 (2017)DO - 10.24843/AJoAS.2017.v07.i02.p11, 2018)
The Quality Test on Soybean Seeds (Glycine max L. Merril) for Grobogan Variety that Produced by Using Applications of 10 Isolats PGPR. This research is aimed to know the ability of isolat Plant Growth Promoting Rhizobakteria (PGPR) producing soybean seed with quality and high seed quality. The complete random plans (RAL) are used in this research. Tens kinds of isolat rhizobakterias and 1 control (without rhizobakteria) are tested. Observation is done toward variable of sprouts’ energy, vigor (energy supplying), electrical conductivity, ratio of seed coat, and vigor of seeds growth (tall, number of leafs, dry weight for oven on ground, and dry weight for roots). The outcome shows of roots that 10 isolat rhizobakterias are able to improve the seed yield and soybean seed quality. 10 isolat rizobakterias produce soybean seeds with sprouts’ energy > 80% to fulfill seed quality standard “international seed testing association (ISTA)”. Having three isolats which are effective namely, R35 (it is isolated from cajanus cajan’s root), R3 (it is isolated from stylosanthes guianensis’s root), and R26 (it is isolated from solanum nigrum’s root). Three of those isolats produce high harvest namely R35 (10.4g), R3 (10.10g), R26 (10.86g). Those three isolats also produce seed with physical quality and high physiology.